Emotional (Dys)regulation in University Students. When Mobile Device Addiction takes its Toll - Castillo Riquelme, Víctor (2023)
The research addresses the link between emotional dysregulation, nomophobia, and Instagram addiction in Chilean university students. A quantitative study of correlational scope was conducted with a non-experimental cross-sectional design. The sample consisted of 218 university students from south-central Chile, who answered the Difficulties in Emotional Regulation Scale (DERS-E), the Nomophobia questionnaire NMP-Q, the Berger Instagram Addiction Scale (BIAS) and reported some parameters of their Instagram account activity. The results account for multiple correlations between nomophobia and Instagram addiction with all dimensions of emotional dysregulation. The number of followers and posts on the Instagram platform did not correlate with the dimensions of emotional dysregulation, although they did show correlations with nomophobia and Instagram addiction. The number of followers, on the other hand, showed correlations with some dimensions of emotional dysregulation. The article closes with a discussion of the implications of the excessive use of mobile devices on the mental health and functioning of university students.